OBSERVATIONS ON THE BIOLOGY AND FISHERY OF THE INDIAN MACKEREL RASTRELUGER KANAGURTA (CUVIER) FROM ANDAMAN ISLANDS - Luther, G (Indian Journal of Fisheries, 2011)
Rastrelliger kanagurta (Cuvler) seems to spawn in the sea around the AndamanIslands from October to April, an individual fish releasing about three batches of eggs in aseason, the time interval between successive spawnings being about one mouth. Morettam 50 % of the fish are raatute at the total length range of 250-259mm. the size offish at completion of one to five years of life provisionally is estimated as 148mm, 218mm,265mm, 302 mm and 330mm respectively; A higher average growth rate of 22 mm permonth was obtained for juveniles up to 110 mm total length. The growth checks foundin scales have been considered to be the spawning marks. The length-weight relationshipof the species has beeii estimated. The fish feed mainly on planktonic copepodsand other crustaceans. The main mackerel fishery season around the Andaman Islandslasts for four months from May to August, when about 60% of the annual mackerelcatch is landed. About 90% of the mackerel in the commercial catches ranged in size between21 cm and 29 cm of which fish in the 21-24 cm total length range constitutedabout 60%. Whereas the mackerel fishery season along the west coast of India coincideswith the post SouthWest Monsoon period, in the Andamans it coincides with the midSouth-West Monsoon Season